A Survey on Medicinal Plant Knowledge among the Indigenous Communities (Tamilians) in the Delta Regions of Tamil Nadu, India. Issue 1 (2nd January 2022) - Srinivasan, Prabhu; Subramaniyan, Vijayakumar; Gk, Thilaka; Krishnasamy, Karthikeyan; Jeyalachagan, Sureshkumar; Palani, Manogar
ABSTRACT: The local people of the delta region of Thanjavur (Tamil Nadu, India) were surveyed to explore the therapeutic medicinal plants used in folk medicine in the study area. The people belonged to four agricultural rural villages in the study region. The medicinal plants data was validated using frequency citation (FC), relative frequency of citation (RFC), use value (UV), relative importance (RI), cultural importance index (CIi), informant agreement ratio (IAR), informant consensus factor (IFC) and fidelity level (FL). The survey identified 77 indigenous plants from 43 families, of which Fabaceae was used 12% followed by Rutaceae (6%), Lamiaceae and Cucurbitaceae (each 5%), Solanaceae (5%) and others (63%), used for treating 20 ailment categories. Among plant parts, leaves were the most used in the form of powder. Acorus calamus, Bauhinia racemosa, Borassus flabellifer, Myristica fragrans, Sphaeranthus indicus, Withania somnifera and Cissampelos andromorpha warrant further pharmacological investigations.